(untitled) (American Journal of Innovation in Science and Engineering, 2025)
The evolution of Artificial Intelligence (AI) in healthcare presents a unique blend of opportunities and challenges, particularly in enhancing healthcare delivery across important healthcare domains. These developments makes this review an interesting one as it explores AI’s capacity to improve healthcare by making processes like drug discovery faster and more cost-effective, enabling early disease detection, tailoring healthcare to individual patient needs and continuous health monitoring. The paper examines the diverse applications of AI tools in healthcare across five (5) key domains (disease diagnosis and prognosis, drug discovery, precision medicine, clinical decision support, and smart wearables), highlighting their role in improving diagnostic accuracy, personalising treatment plans, aiding in medical decision-making, forecasting patient health trends and facilitating continuous patient monitoring. The insights from this review lead to a balanced perspective on AI’s role in healthcare, emphasising the importance of adopting AI in a patient centric and ethically responsible manner while navigating the challenges that comes with it.